Sex differences in onset and prevalence of 108 diseases and multimorbidity across lifespan in Yichang, China: quantitative analysis of real-world linked electronic health records - Paul A Scuffham; Maigeng Zhou; Chen Wang; Xin Xu; Ruitai Shao; Ji Zhang; Luzhao Feng; Enying Gong; Chi Hu; He Xu; Xunliang Tong; Zuolin Lu; et al. (BMJ Open, 2025)
Objective The magnitude and persistence of diseases and multimorbidity between females and males are different. This study comprehensively quantified sex differences in the onset and progression of 108 major physical and mental diseases to multimorbidity through adulthood in Chinese population.Design Quantitative analysis of real-world linked electronic health records.Setting Linked health records from 160 health facilities across primary, secondary and tertiary healthcare, comprising routinely collected electronic health records from the whole urban residents of Yichang, China between 1 January 2016 and 31 December 2019.Participants 684 455 urban residents aged 20 years and above with documented health records during the study period.Main outcomes measures The cumulative incidence, relative risks (RR) and 95% CIs, period prevalence, median age at disease diagnosis and the prevalence of multimorbidity of 108 major physical and mental diseases were computed. All analyses were stratified by sex and age groups.Results The analysis included 684 455 individuals (54.8% females, mean age: 46.9), among whom 46.3% had multimorbidity, with a higher prevalence in females (47.6%) than males (44.9%). The chronological disease map revealed stark differences between females and males, with notable lower risk of obstructive sleep apnoea-hypopnoea syndrome (OSAHS, RR: 0.03, 95% CI: 0.01 to 0.11) for young adults, oesophageal cancer (RR: 0.02, 95% CI: 0.0 to 0.17) for mid-age adults and remarkable higher risk of lupus (RR: 8.8, 95% CI: 2.7 to 29.0) for older adults of females. Males exhibited an incidence surge in hypertension, diabetes, coronary disease and chronic obstructive pulmonary disease a decade earlier than females, while females had a life-long higher prevalence in immune-mediated diseases and urinary disorders. For the new incident diseases, the manifestation of eating disorders, anaemia and urinary incontinence was recorded 20 years earlier in females; whereas, males were diagnosed with hyperuricaemia, OSAHS and schizophrenia at younger ages.Conclusions The significant variations in disease nature and trajectory between sexes underscore the urgent needs for tailored prevention strategies and appropriate health resources allocation. Sex differences in disease profile should be considered to delay disease and multimorbidity progression, ultimately promoting health equity.